Change in biochemical profile of rats under carbon tetrachloride-induced liver injury - Галенова, Тетяна Іванівна; Ракша, Наталія Григорівна; Савчук, Олексій Миколайович (ScienceRise: Biological Science, 2016)
The carbon tetrachloride-induced rat model of liver injury was described. Changes in serum biochemical parameters indicate a progressive process of the hepatocyte destruction and intrahepatic cholestasis, which most likely is the result of oxidative stress activation in response to toxicants. Our results also demonstrated an imbalance of pro- and anti-inflammatory cytokines under conditions of tetrachloroethane intoxication